Financing green transition: The role of bank-nonbank partnerships - Gallo, Angela; Park, Min (Journal of Financial Intermediation, 2026)
We document a significant role for nonbanks in financing the green transition following the Paris Agreement, primarily through lending partnerships with banks. Using textual analysis to identify green loans, we show that nonbanks participate in a greater number of green syndicated loans and commit larger amounts in response to corporate demand for green financing. Such nonbank investment in green loans is associated with more favorable loan terms and is consistent with a nonbank-led expansion in credit supply rather than bank-driven risk offloading. Nonbank investment is highly sensitive to policy signals, suggesting that regulatory transition risk is a key driver. Overall, our findings show the potential for nonbanks to support the transition but only under credible political commitment to climate goals.